ANALISIS SALURAN PEMASARAN USAHA GULA AREN (Studi Kasus : Desa Puudongi Kecamatan Polinggona Kabupaten Kolaka) - Campina Illa Prihantini; Yuli Purbaningsih; Alda Sari; Helviani; Fikram; Umbu Joka; Muh. Ilham Taufik; Sri Hardina (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
This study aims to determine the marketing channels and marketing margins of palm sugar for each level of the institution in Puudongi Village, Polinggona District, Kolaka Regency. This research is a case study research. Primary data is obtained directly from palm sugar processing farmers while secondary data is in the form of statistical data, annual reports, research reports, journals and other data related to the topic of this study. The sample in this study were all palm sugar business actors in Puudongi Village as many as 7 people. The results showed that there are three main marketing channels in marketing palm sugar in Puudongi Village. . Marketing channel I is the most inefficient marketing channel because it has the longest marketing channel among the other two marketing channels.